2009
DOI: 10.1111/j.1399-0039.2008.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G polymorphism and in vitro fertilization failure in a Polish population

Abstract: To investigate whether human leukocyte antigen-G (HLA-G) gene polymorphism is associated with in vitro fertilization (IVF) failure, we sequenced exons 2-4 of the HLA-G gene in 50 couples with three or more IVFs (including 10 couples with five or more IVFs) and 58 control fertile couples from a Polish population. Of the 10 different HLA-G alleles identified in our study subjects, neither allele was found to be associated with IVF. We also genotyped 50 couples with IVF and 71 control couples for the -725C>G vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
(40 reference statements)
2
26
1
1
Order By: Relevance
“…Some studies have reported an association between the ϩ14 bp/ϩ14 bp HLA-G genotype or the ϩ14-bp HLA-G allele in women and risk of RSA [62][63][64] or unsuccessful in vitro fertilization treatment [63,65]. A study by Tripathi and co-workers indicated a significant increase in the number of heterzygotes for the 14-bp polymorphism in RSA women versus control women [66].…”
Section: Hla-g Polymorphism In Relation To Pregnancy Complicationsmentioning
confidence: 94%
“…Some studies have reported an association between the ϩ14 bp/ϩ14 bp HLA-G genotype or the ϩ14-bp HLA-G allele in women and risk of RSA [62][63][64] or unsuccessful in vitro fertilization treatment [63,65]. A study by Tripathi and co-workers indicated a significant increase in the number of heterzygotes for the 14-bp polymorphism in RSA women versus control women [66].…”
Section: Hla-g Polymorphism In Relation To Pregnancy Complicationsmentioning
confidence: 94%
“…reviews 17 studies that have reported on the 14-bp ins/del polymorphism in exon 8 of HLA-G and its association with various pregnancy complications. Out of five studies that focused on recurrent spontaneous abortion (RSA) [8,9,[11][12][13], four reported a link with mRNA expression [14][15][16][17], four with pre-eclampsia [10,18,19], three with IVF treatment [20][21][22] and one with birth weight [23].…”
Section: Introductionmentioning
confidence: 99%
“…allele HLA-G*01:01 only 4 out of the 33 SNPs within the coding region of HLA-G are related to an amino acid exchange, which do present frequencies above 1% in population studies (4)(5)(6)(7)(8)(9) . One of them is located at codon 31 in exon 2 exchanging a threonine for serine, being typical for the G*01:03 allele (Table 1 ).…”
Section: ----------------------------A -----T ---------G*01:01:03 ---mentioning
confidence: 99%